Development,testing and fluid interaction simulation of a bioprosthetic valve for transcatheter aortic valve implantation - Kemp, Iain Henry (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--Stellenbosch University, 2012.